2014
DOI: 10.1097/ijg.0b013e31829e5635
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Continuous 24-Hour Intraocular Pressure Monitoring for Assessment of Prostaglandin-induced Pressure Reduction in Glaucoma

Abstract: Our results suggest that the current CLS technique cannot be clinically used to monitor IOP decrease induced by topical medication in glaucoma, and has limited value in identification of transient IOP elevation periods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
51
0
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(58 citation statements)
references
References 11 publications
0
51
0
3
Order By: Relevance
“…It was reported that glaucoma medication could make the circadian IOP fluctuation smaller 20. Holló et al reported that a CLS could not measure the effect of topical medication or body position 21. Adherence of a CLS to the cornea might alter the effects of topical medications.…”
Section: Limitationsmentioning
confidence: 99%
“…It was reported that glaucoma medication could make the circadian IOP fluctuation smaller 20. Holló et al reported that a CLS could not measure the effect of topical medication or body position 21. Adherence of a CLS to the cornea might alter the effects of topical medications.…”
Section: Limitationsmentioning
confidence: 99%
“…To understand why our results were contrary to current knowledge, we divided the total wake period into wake period before sleep and wake period after sleep. The CLS values during the wake period after sleep were higher than the values during the sleep period and the wake period before sleep in both sleeping positions, revealing an increase in CLS output or ‘upward drift’ with prolonged CLS wear (Figures 1A and B), a phenomenon of unknown cause recently noted by others 10 15 16. We also found GAT-IOP readings were higher than baseline after CLS removal in seven patients in at least one session with a mean increase of 1.6 mm Hg in the flat position compared with 2.8 mm Hg in the 30° head-up position.…”
Section: Discussionmentioning
confidence: 51%
“…Ocular hypotensive medications mostly reduce IOP in absolute terms with a smaller effect on modulating the 24-h IOP rhythm. These changes may not be readily observable with the CLS [39]. A more appropriate use of the CLS may be in investigating the effect of laser interventions, surgery [40,41], and lifestyle [42] on the 24-h IOP.…”
Section: Temporary Intraocular Pressure Monitoringmentioning
confidence: 95%